Evidence of polycyclic aromatic hydrocarbon biodegradation in a contaminated aquifer by combined application of in situ and laboratory microcosms using 13C-labelled target compounds. (1st February 2015) - Bahr, Arne; Fischer, Anko; Vogt, Carsten; Bombach, Petra
Abstract: The number of approaches to evaluate the biodegradation of polycyclic aromatic hydrocarbons (PAHs) within contaminated aquifers is limited. Here, we demonstrate the applicability of a novel method based on the combination of in situ and laboratory microcosms using 13 C-labelled PAHs as tracer compounds. The biodegradation of four PAHs (naphthalene, fluorene, phenanthrene, and acenaphthene) was investigated in an oxic aquifer at the site of a former gas plant. In situ biodegradation of naphthalene and fluorene was demonstrated using in situ microcosms (BACTRAP ® s). BACTRAP ® s amended with either [ 13 C6 ]-naphthalene or [ 13 C5 / 13 C6 ]-fluorene (50:50) were incubated for a period of over two months in two groundwater wells located at the contaminant source and plume fringe, respectively. Amino acids extracted from BACTRAP ® -grown cells showed significant 13 C-enrichments with 13 C-fractions of up to 30.4% for naphthalene and 3.8% for fluorene, thus providing evidence for the in situ biodegradation and assimilation of those PAHs at the field site. To quantify the mineralisation of PAHs, laboratory microcosms were set up with BACTRAP ® -grown cells and groundwater. Naphthalene, fluorene, phenanthrene, or acenaphthene were added as 13 C-labelled substrates. 13 C-enrichment of the produced CO2 revealed mineralisation of between 5.9% and 19.7% for fluorene, between 11.1% and 35.1% for acenaphthene, between 14.2% and 33.1% for phenanthrene, and up to 37.0% for naphthalene over a period of 62 days. Observed PAH mineralisation rates ranged between 17 μg L −1 d −1 and 1639 μg L −1 d −1 . The novel approach combining in situ and laboratory microcosms allowed a comprehensive evaluation of PAH biodegradation at the investigated field site, revealing the method's potential for the assessment of PAH degradation within contaminated aquifers. Graphical abstract: Highlights: Novel approach combined in situ and laboratory microcosms. Biodegradation of naphthalene and fluorene was assessed by in situ microcosms. In situ microcosms enable to enrich microbial communities for laboratory microcosms. Mineralisation of naphthalene, fluorene, phenanthrene, acenaphthene was quantified.